Sustainable Catalysts from Industrial FeO Waste for Pyrolysis and Oxidation of Hospital Polypropylene in Cartagena (2024)
During the COVID-19 pandemic, polypropylene waste generated in hospitals increased significantly. However, conventional strategies for the final disposal of environmental waste, such as incineration, proved inefficient due to the generation of toxic chemical species. In this research, these PP wastes were mixed with 1.5, 20, 150, 200, and 400 mg of iron oxide (FeO), extruded, and pelletized to obtain samples HW-PP-0, HW-PP-1, HW-PP-2, HW-PP-3, and HW-PP-4, respectively. XRF, TGA, and GC-MS characterized these samples. The samples were subjected to pyrolysis and thermo-oxidative degradation with controlled currents of nitrogen and oxygen. The characterization of the gases resulting from pyrolysis was carried out with a GC-MS, where the results showed that HW-PP-0 (mixed with 1.5 mg of FeO) presented the highest concentrations of alkanes (35.65%) and alkenes (63.7%), and the lowest levels of alkynes (0.3%), alcohols (0.12%), ketones (0.04%), and carboxylic acids (0.2%). The opposite was observed with the hospital waste HW-PP-4 (mixed with 400 mg of FeO), which presented the highest levels of alkynes (2.93%), alcohols (28.1%), ketones (9.8%), and carboxylic acids (8%). The effect of FeO on HW-PP-O during thermo-oxidative degradation generated values of alkanes (11%) and alkenes (30%) lower than those during pyrolysis. The results showed the catalytic power of FeO and its linear relationship with concentration. This research proposes the mechanisms that can explain the formation of different functional groups of various molecular weights which allow us to understand the presence of alkanes, alkenes, alkynes, alcohols, ketones, and carboxylic acids.